Crafting qualitative research questions the prequel to design - Baker, Elizabeth A. (Elizabeth Anne) 1960- (Qualitative research methods series, 2022)
"The essence of research design is the ability to articulate your research question. The research question is the precursor to the study, and a well-crafted question encapsulates all of the design elements for that study. Based on more than 20 years of experience advising doctoral students, author Elizabeth (Betsy) A. Baker forged a design heuristic which she introduces in this book. She starts by dissecting the anatomy of a qualitative research question, outlines the role of paradigms in research design, describes strategies to use the anatomy as a design heuristic, and provides sample cases that track the decisions two researchers made while formulating a qualitative question. The book concludes with advice on how to move from the research question to the proposal. Throughout, the author provides handy worksheets that readers can complete as they work on crafting their own research question"--Provided by publisher.